KEBENARAN ILMIAH DALAM PEMIKIRAN THOMAS S. KUHN DAN KARL R. POPPER: SUATU KAJIAN HERMENEUTIKA DAN KONTRIBUSINYA BAGI MASA DEPAN ILMU - Fuad Fuad; Koento Wibisono S.; P. Hardono Hadi (Jurnal Filsafat "WISDOM", 2015)
The scientific truth can be identified on the Kuhn's normal science as a period of scientific progress, and on the Popper's verisimilitude (the truthlikeness). The Kuhn's thought is a phenomenological hermeneutics due to his understanding of the scientific truth according to the phenomenon of scientific progress, and otherwise, the Popper's is an ontological hermeneutics which acknowledges the absolute truth beyond the scientific explanation. The essential similarity of Kuhn and Popper's hermeneutics is justifying the scientific truth as a relative ideal one (never be the absolute one), and the fundamental difference of both of them caused by Kuhn's hermeneutics based on a descriptive approach and Popper's by the normative one. The Kuhn and Popper's hermeneutics can be contributed to be a philosophical foundation of science, namely: the scientific investigation area (ontological foundation), the dialectic of scientific progress (epistemological foundation), and toward the absolute-transcendental truth (axiological foundation). The hermeneutics can also be contributed to reintegrate science and philosophy, as a correlation and interconnection entity of empirical and metaphysical dimension, and can spontaneously be an understanding frame of the demarcation of science (a system of empirical knowledge) and philosophy (a system of metaphysical one). The hermeneutics can be contributed to implement the integration of Natural Sciences and Humanities (and Social Sciences) in Indonesia, as an IPTEK development strategy which is relevant to the ethical values of the Pancasila's.